(untitled) (Jurnal Manajemen dan Ekonomi (JME), 2025)
This study aims to find out information about the wants and needs of Kamsia Boba Singaraja franchise consumers by using the Quality Function of Deployment (QFD) method and choosing alternative decisions for developing Kamsia Boba Singaraja products. This research was located at one of the Kamsia Boba stands located at Jl. Ahmad Yani No.53 Singaraja. Data collected using interview techniques, with data analysis techniques Qualitative Analysis of the Miles &Huberman model and Analysis used for the QFD model is the House of Quality (HOQ). The subjects of this research are Employees, Owners, and consumers of Kamsia Boba Singaraja. The results of this study indicate that Kamsia Boba’s product design attributes are in accordance with the tastes and needs of consumers, among others in terms of taste, packaging, price, service and consumer satisfaction with these products. Consumer needs include, according to consumer tastes to taste variants, toppings, packaging that are spilling and spilling, competitive prices with similar products, appropriate price offerings, friendly service and the appearance of clean and neat sellers, fast service and satisfaction with product purchase decision. The result of making the House of Quality matrix is consumer priority. The final result after going through several stages in making the HOQ matrix is prioritization. The result of determining product priorities is product development in the appropriate price offer.